Updated studies on Ampelozizyphus amazonicus, a medicinal plant used in the Amazonian Region - F. Amaral, Ana Claudia; P. Ferreira, José Luiz; de Moura, Dominique F.; R. Carvalho, Junior; T. Ohana, Débora; Echevarria, Aurea; do Rosário, Virgilio E.; Lopes, Dinora; de A. Silva, Jefferson Rocha (Pharmacognosy Reviews)
The Ampelozizyphus genus (Rhamnaceae family) is endemic in the Amazonian region and in Brazil. It occurs in the states of Amazon, Pará and Roraima, and is found in undergrowth vegetation, clayey-sandy to sandy soil, and occasionally in secondgrowth area and in non-flooded humid forests. Ampelozizyphus amazonicus is a liana or shrub with large leaves and an extensive radicular system. Popularly this species is considered stimulant and energetic, increasing the organic resistance. It is known as saracura-mirá, cervejeira and cerveja de índio, among other common names. The aqueous preparations with the roots are commonly used in traditional medicine as anti-inflammatory, antidote to snake venoms and for the prevention of malaria. The phytochemical studies have reported the presence of triterpenoids, steroids and saponins. Chromatographic profiles of the beverage showed that the aqueous preparations were rich in saponins. The pharmacological studies made with this botanical species indicate activities such as: malaria prophylaxis, trypanocidal, antifungical, antiviral and antibacterial. This work presents updated data related to the botany, chemistry and pharmacology of A. amazonicus, which emphasize their wide use in the folk medicine in the Amazonian region.
Keywords: Rhamnaceae; Ampelozizyphus amazonicus; malaria; chromatography; pharmacology